Empiricism in nursing practice - Elvio Fernández Toledo (Acta Médica del Centro, 2015)
Nursing, like any profession, is a social product that takes, in every period of history, so that it is possible in the circumstances in question. A literature review was conducted to analyze the influence of empiricism in practice and nursing education in Cuba. Concepts, approaches and positions of the author are highlighted. It was considered thaº zxciop`xz  t the empirical character that has always marked nursing practice contributes greatly to knowledge acquisition that taxed to  improvement of care; however, teaching and professional practice of nursing should not be advocated through empiricism. The timely intervention of teachers in improving the performance of learners, from the laboratory to the patient, strengthen, among others, the value of responsibility in them, which will refine the methods, techniques, theories and models based nursing.